Analysis of Training Needs for Developing Teaching Modules Based on Didactical Situation Analysis - Shafarwati, Dwi Ajni; Johan, Riche Cynthia (Jurnal Prima Edukasia, 2025)
Pedagogic competence is one of the most important competencies that teachers must have because it is directly related to the ability to manage learning effectively. In Indonesia, this competency still needs to be improved, especially in terms of teacher motivation to develop themselves through training in order to create quality education that is oriented towards the future of students. This study aims to identify the gap between actual performance and desired performance of teachers in developing pedagogical competence, especially in the preparation of teaching modules based on didactical situation analysis. The approach used was a mixed-methods study with an unbalanced convergent model. Data were collected through interviews, document analysis, and questionnaires, then analyzed separately and compared. The results show that teachers still tend to fulfill administrative aspects in preparing teaching modules without considering the characteristics of students and the complexity of the material. Therefore, special training is needed so that teachers are able to optimally improve pedagogical competence through didactical situation analysis.